HTLV-1 infection in acute t- lymphocytic leukemia/lymphoma - Barouqa, Mohammad; Reyes Gil, Morayma; Sekhri, Radhika; Popoola, Mojisola; Ding, Juan; Wang, Yanhua (Autopsy and Case Reports, 2021)
Adult T- lymphocyte leukemia/ lymphoma (ATLL), described by Uchiyama et al. in 1977, is a distinct neoplasia of peripheral T-lymphocytes caused by human T-cell lymphotropic virus type 1 (HTLV-1). The authors describe the case of a 75-year-old female patient who presented with fever, chills, and altered mental status. The peripheral blood morphology showed large atypical lymphocytes with multilobed nuclei and flow cytometry consistent with ATLL. The authors discuss the pathophysiology, differential diagnosis, and subtypes of ATLL in addition to the diagnostic approach using flow cytometry when bone marrow biopsy is not available and modalities of treatment.